Bifunctional Catalyst for Liquid–Solid Redox Conversion in Room‐Temperature Sodium–Sulfur Batteries. Issue 8 (2nd May 2022) - Wu, Jiahui; Yu, Zuxi; Yao, Yu; Wang, Lifeng; Wu, Ying; Cheng, Xiaolong; Ali, Zeeshan; Yu, Yan
Abstract : Room‐temperature sodium–sulfur (RT Na–S) batteries are one of the most promising large‐scale energy storage systems due to their high energy density and abundant Na reserve. However, the main challenges of poor rate performance and unsatisfactory capacity ascribing to sluggish conversion reaction kinetics and severe shuttling effect of long‐chain sodium polysulfides (NaPSs) retard the practical application. An ideal RT Na–S cathode host should concurrently incorporate strong adsorption capability and high catalytic activity. Herein, a bifunctional catalyst is designed, i.e., cobalt sulfide–selenide heterostructure in multichannel carbon nanofibers (denoted as CoS2 –CoSe2 @CNFs), as sulfur host for RT Na–S batteries. This unique catalyst combines the advantages of CoS2 with high adsorption capability toward soluble sodium polysulfides and CoSe2 with efficient catalytic activity to promote the liquid–solid conversion process. As a result, the S/CoS2 –CoSe2 @CNFs cathode achieves a high initial capacity (1295 mAh g −1 at 0.1 A g −1 ), long cycling stability (749 mAh g −1 after 200 cycles at 1 A g −1 ), and outstanding rate capability (866 mAh g −1 at 3 A g −1 ). This work demonstrates a new bifunctional design strategy from theoretical and experimental aspects for high‐performance RT Na–S batteries. Abstract : An effective and controllable approach is developed to prepare the CoS2 –CoSe2 @CNFs as high‐performance bifunctional catalysts for room temperature sodium–sulfur (RT Na–S) batteries. Benefitting from the unique cobalt sulfide–selenide heterostructure and the synergistic effect between CoS2 and CoSe2, the S/CoS2 –CoSe2 @CNFs cathode exhibits superior electrochemical performance.